Environmental persistence and the efficacy of commonly used disinfectants on vancomycin-resistant enterococcus (vre) isolated from chickens and humans - Yerima, Adamu Abubakar (2012)
Vancomycin-resistant enterococci (VRE) are well-known ascendant nosocomial pathogens and farm animals have been implicated as the source and reservoir for VRE in humans. In Malaysia, VRE had been a great concern to poultry farmers that export their products to Singapore due to the restriction on export of only VRE-free poultry products. The present study was conducted to provide more understanding on the duration of survival of VRE in the Malaysian local weather and the factors that may affect its survival. The specific objectives of the study are: to ascertain the viability and sustainability of VRE isolates in the local Malaysian environment, to determine the factors that contributes to the survival of the isolates in the environment and to determine the efficacy of commonly used disinfectants available to farmers on the isolates.Survival and surface experiment were performed using 10 isolates of VRE; Enterococcus faecalis (two each from human and chicken, one reference strain) and Enterococcus faecium (two each from human and chicken, one reference strain) carrying vancomycin resistance gene. In the first study, the abilities of the isolates to survive when dried on wooden surfaces in a typical Malaysian climate of high temperature and high relative humidity (RH) of 30oC ± 2oC and 80% ± 10% RH and examined the influence of organic soiling on the survival of the isolates. The results revealed that all the isolates survived for at least 4 weeks when devoid of protective influences of substances such as protein (clean condition) and for a minimum of 8 weeks in the presence of organic soiling (soiled condition). After 4 weeks, the isolates survived with a colony count of 6.80 x 102 – 5.06 x 103 CFU/ml in clean condition and in a relatively higher colony counts of 1.00 x 103 – 2.02 x 104 CFU/ml in soiled condition. Four of the isolates survived till the end of the study (16 weeks). The isolates had an overall decay rate of -0.13 irrespective of source (human or chicken), condition (clean or soiled) and species (E. faecalis or E. faecium). The decay rates did not vary significantly by the source of organism (p = 0.48) but varies significantly between species (p = 0.001). E. faecium have a higher decay rate of -0.16 than -0.13 for E. faecalis in clean condition and the values of -0.12 and -0.11 in soiled condition. The decay rates also varies by condition (p=0.001) with the isolates showing decay rates of -0.144 in clean condition and -0.118 in soiled condition.This signifies that the presence of soiling as obtainable on farms significantly increases the survival time and number of surviving VRE. In the second study, the effect of organic soiling on the disinfection procedure and the efficacy of in-use concentration of a few commonly used disinfectants (Lindores*-30®, Omnicide® and EcosTimsen®), was evaluated using the European surface test. All disinfectants tested have an intermediate activities against the organism (ME consistently between 2 and 5) except for Omnicide® which exhibited low activity on stainless steel surface in soiled condition (MEs consistently between 0.5 and 3).In clean condition, Ecos Timsen® had the highest ME value of 5.29±1.44 while Omnicide® has the least ME value of 2.38±0.58for E. faecalis. On wooden surfaces, Omnicide® showed the highest ME value of 3.53±0.49 for E. faecalis with Lindores-*30® showing the least ME value of 2.84±0.24 for E. faecium in clean condition. In soiled condition, all tested disinfectants exhibited a significantly reduced activity with lower ME values. Omnicide® showed the highest value of 2.43±0.57 for E. faecalis and Ecos Timsen® have the least ME value of1.53±1.01 for E. faecium on stainless steel surface. On wooden surface, the highest ME value was observed when using Ecos Timsen® (2.27±0.58) for E. faecium. Lindores-*30® have the least value 1.11±0.49 for E. faecium. Therefore, this study signifies that the commonly used disinfectants do not altogether eliminate VRE from the farm environment especially in the presence organic soiling and that the rate of effectiveness of the disinfectant varies with type of surfaces where it is being applied. This study has improved on the knowledge on the survival of VRE in the Malaysian climate of high relative humidity and temperatures. Furthermore the in-use concentration of some commonly used disinfectant does not altogether eliminate VRE from the farm environment especially in the presence of organic soiling which markedly reduced the activity of the disinfectants. The study has provided an insight that can be further enhanced in devising means by which VRE persistence in poultry farms can be mitigated.